Evaluation of Radiotherapy Practice in Patients Aged over 80: A Retrospective Study - Demir, Harun; Babalıoğlu, İbrahim; Akkar, İlyas; Kızılarslanoğlu, Muhammet Cemal (South Asian Journal of Cancer, 2025)
The study aims to evaluate the survival outcomes, survival-related prognostic factors, and treatment compliance in cancer patients aged ≥80 years treated with radiotherapy (RT).The records of 76 patients who received RT at a single center between August 2021 and May 2024 were retrospectively evaluated. Patient and tumor characteristics and treatment details were collected from medical records.The median age of the patients was 83 years (range: 80–92 years). According to the purpose of RT, palliative (53.8%), definitive (18.4%), and adjuvant (15.8%) RT were most frequently administered, respectively. The median overall survival (OS) in all patients was 10 months. The median OS in patients receiving curative (definitive and adjuvant RT) and palliative RT was 25.1 and 7.2 months, respectively. Poor performance status (PS), leukocyte count prior to RT, compliance, and hospitalization status in the curative group and poor PS, RT compliance, hospitalization status, and new distant recurrence in the palliative group were associated with decreased OS. The majority of patients showed full compliance with the RT process (69.7%). The rate of full compliance with the treatment process was significantly higher in patients with good PS and receiving outpatient treatment. RT-related high-grade toxicity (grade 3–4) was not observed.This study demonstrates that RT can be used effectively and safely for both palliative and curative purposes in cancer patients aged ≥80 years. The optimization of patient selection and ultimately improvement of treatment outcomes will be facilitated by the support of these results with multicenter studies.
Keywords: older patients; malignancy; octogenarians; overall survival; radiotherapy